Online Neurobiology Course - An Emergent Plan during the Pandemic - Kore, Smitha Elizabeth; Simon, Miriam Archana; Vishwakarma, Nitin; Siddiqui, Najam (Journal of Liaquat University of Medical & Health Sciences, 2023)
OBJECTIVE: To obtain student's perceptions of the online neurobiology course conducted during the pandemic. METHODOLOGY: A cross-sectional survey was conducted among the MD3 (year 4) students. One hundred thirty-three students enrolled in the neurobiology course submitted their responses to the study. The survey was administered as a questionnaire on a five-point Likert scale to record the student's perception of the different aspects of the course. Descriptive and Chi-square analyses were employed among the variables. Data was statistically analyzed using IBM SPSS version 22. Descriptive analysis was used to analyze students' perceptions of how the online course was administered. The Shapiro-Wilk normality test results for all survey items (p=0.000) indicate that participant responses were not normally distributed. Chi-square (Inferential statistical procedures) were employed to test hypotheses exploring associations among variables. RESULTS: The feedback analysis reflected that the students reacted positively to the modified teaching interventions and assessments. Most of the students were satisfied with the mode of delivery of the course and rated the course highly. CONCLUSION: The survey results indicated that the online neurobiology course successfully addressed the course learning outcomes. Lessons from these experiences and taking advantage of educational technologies can help design technology-aided blended learning courses to enhance teaching in the upcoming academic years.